2011
DOI: 10.17221/69/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Vis/NIR hyperspectral imaging for detection of hidden bruises on kiwifruits

Abstract: Lü Q., Tang M.-j., Cai j.-r., Zhao j.-w., Vittayapadung S. (2011): Vis/NIR hyperspectral imaging for detection of hidden bruises on kiwifruits. Czech j. Food Sci., 29: 595-602.It is necessary to develop a non-destructive technique for kiwifruit quality analysis because the machine injury could lower the quality of fruit and incur economic losses. Bruises are not visible externally owing to the special physical properties of kiwifruit peel.we proposed the hyperspectral imaging technique to inspect the hidden br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The baseline band selection method was principle components analysis (PCA), which is an effective data reduction technique that is used frequently in hyperspectral data analysis [6]. In PCA, a human manually selects a principle component (i.e., PC2 as shown in Figure 6(a)) that visualizes the abnormal region clearly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline band selection method was principle components analysis (PCA), which is an effective data reduction technique that is used frequently in hyperspectral data analysis [6]. In PCA, a human manually selects a principle component (i.e., PC2 as shown in Figure 6(a)) that visualizes the abnormal region clearly.…”
Section: Resultsmentioning
confidence: 99%
“…Baseline method of band selection by PCA [6]: (a) principal component: PC2 and (b) load function curve of PC2.…”
Section: Figurementioning
confidence: 99%
“…These methods can be divided into four groups, namely a) agglomerativehierarchicalclusteringinaone-step(1) and a two-step procedure (2), b) k-means clustering in a one-step (3) and a two-step (4) procedure, c) multivariateGaussianmixturemodelsinaone-step (5) and a two-step (6) procedure and d) a combination of two of the preceding methods, namelycombinationof(b)and(a) (7),and(b)and(c) (8).…”
Section: Unsupervisedpixelclassificationmentioning
confidence: 99%
“…Baranowski et al 7 useddifferentsupervisedclassificationmethods, suchassupportvectormachines(SVM),functionaltrees, nearest-neighbourclassifiersandregressionmethods,to distinguishbruisedappletissuefromsoundtissueand found that logistic regression gave the best classification resultswith a correct classification rate of 98.8%. Lü et al 8 applied SVM on hyperspectral data from kiwifruit to detect bruiseswith a misclassification rate of 12.5%. Partial least squares discriminant analysis (PLS-DA),asupervisedclassificationmethodbasedonpartial least squares regression (PLSR), 9 was used to classify undamaged, mechanically damaged and microbiological diseased mushroomswith a correct classification rate ofmorethan95% 10 and to classify hazelnuts into four qualityclasseswithmorethan90%accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The classification results were about 93% of the non-bruised apples recognised, and an accuracy of about 86% for detecting bruises. Besides apple, hyperspectral imaging has also been used for the bruise detection of pear (Zhao et al, 2010), cucumber , mushroom (Esquerre et al, 2012;Gowen et al, 2008), strawberry (Nagata et al, 2006) and kiwifruit (Lü et al, 2011). Zhao et al (2010), using PCA and spectral angle mapper classification algorithm, obtained a detection accuracy of 95% for bruise detection on pears.…”
Section: Physical Properties Inspectionmentioning
confidence: 99%